Psychosocial Problems Among Diploma Nursing Students: A Descriptive Study - Rantesigi, Nirva; Agusrianto, Agusrianto; Suharto, Jeane Sriani (Madago Nursing Journal, 2025)
Background: Psychosocial problems among nursing students have become a significant concern in healthcare education. High academic demands combined with clinical practice pressures create vulnerability to mental health issues. This study aimed to describe psychosocial problems among D-III nursing students in Poso. Methods: This descriptive study was conducted among 111 nursing students using the SRQ-29 questionnaire. Data were collected through online forms and interviews over three days. The study focused on identifying neurosis-related psychosocial problems among respondents. Results: The findings revealed that 57 students (51.4%) experienced neurosis problems, while 54 students (48.6%) showed no significant psychosocial issues. Female students showed higher prevalence (52.7%) compared to males (48.6%). The highest proportion of neurosis cases was found among third-year students (56.3%) and those aged 16-17 years (71.4%). Conclusion: More than half of nursing students experience psychosocial problems, primarily neurosis. These findings highlight the need for mental health support programs and counseling services within nursing education institutions.